2020
DOI: 10.3892/etm.2020.8702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of icariin on cell injury and glucocorticoid resistance in BEAS‑2B cells exposed to cigarette smoke extract

Abstract: Glucocorticoids (GCs) exert a therapeutic effect in numerous chronic inflammatory diseases. However, chronic obstructive pulmonary disease (COPD) tends to be GC-resistant. Icariin, a major component of flavonoids isolated from Epimedium brevicornum Maxim (Berberidaceae), significantly relieves symptoms in patients with COPD. However, the mechanism of action remains unclear and further investigation is required to establish whether it may serve as an alternative or complementary therapy for COPD. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 82 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Zhang et al showed that baicalin ameliorated CS-induced airway inflammation in rats by enhancing HDAC2 protein expression and inhibiting the expression of NF- κ B and its downstream target PAI-1 [ 41 ]. Hu et al not only showed that icariin reduced CSE-induced inflammation, airway remodeling, and ROS production but also reported that treatment with the combination of icariin and glucocorticoids could reduce glucocorticoid resistance [ 42 ]. Although TCM has proved to be successful in improving glucocorticoid resistance in COPD, whether the underlying mechanism involves downregulation of PI3K β /AKT signaling and upregulation of HDAC2 expression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al showed that baicalin ameliorated CS-induced airway inflammation in rats by enhancing HDAC2 protein expression and inhibiting the expression of NF- κ B and its downstream target PAI-1 [ 41 ]. Hu et al not only showed that icariin reduced CSE-induced inflammation, airway remodeling, and ROS production but also reported that treatment with the combination of icariin and glucocorticoids could reduce glucocorticoid resistance [ 42 ]. Although TCM has proved to be successful in improving glucocorticoid resistance in COPD, whether the underlying mechanism involves downregulation of PI3K β /AKT signaling and upregulation of HDAC2 expression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that icariin inhibits CSE-induced inflammation, ROS production, and airway remodeling via mitigating glucocorticoids resistance in CSE-exposed BEAS-2B cells [ 35 ]. In addition, nobiletin exhibited protective effects in decreasing the production of TNF- α , IL-6 via restraining activation of NF- κ B signaling in the LPS-induced acute lung injury mice model and LPS-stimulated A549 cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that icariin can not only increase expression of the anti-inflammatory factor interleukin-10 but also decrease expression of various proinflammatory factors IL-8 and tumor necrosis factor- α . Besides this, icariin can regulate the expression of Glucocorticoids (GC) resistance-related factors, which was beneficial for reversing GC resistance in COPD [ 69 , 70 ]. Regarding the administration ways, intravenous mode was the preferred mode of administration (6 studies), followed by intermuscular administration (1 study).…”
Section: Discussionmentioning
confidence: 99%